A Root Cause Failure Analysis (RCFA) on the Primary Air Fan (Pa Fan) Motor at Pangkalan Susu Power Plant - Absalom Andika Simamora; Siti Anisa; Solly Aryza (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
PA Fan (Primary air fan) is equipment that functions to suck air from the atmosphere which aims to supply air to the coal pulveriser to dry the coal and transfer the coal ash to the boiler. PA Fan in operation has tripped with an indication on the protection panel OP_ROC. This ROC indication appears due to an indication of a short circuit to ground or an imbalance of currents between phases which causes a zero connection current. When the local inspection was carried out, it was found that there was a burnt insulator on the S side phase. This resulted in the motor losing one phase and causing ROC (Residual Over Current) protection on the 6 kV protection module to work.